Aplikasi Evaluasi Layanan Mahasiswa Studi Kasus STMIK Bandung - Mina Ismu Rahayu; Rizky Irmawan Rahayu; Dedy Apriadi (LPPM STMIK Bandung, 2021)
The success of an activity depends largely on user satisfaction. To measure this, evaluations at the end of each process are essential, typically conducted through questionnaires. The results of these questionnaires can then be analyzed to determine the overall success of the service provided. Student satisfaction with the services they receive has a significant impact on the performance of a higher education institution, as students are the primary stakeholders in the sustainability of the institution. The Academic Service Evaluation Application is a web-based platform designed to meet the needs of processing evaluation questionnaire data, including learning evaluations, student services, and tracer studies. This application is developed to simplify the analysis of student satisfaction with various services provided by higher education institutions. It includes features for limiting respondents based on the type of questionnaire and generating summary reports for specific questionnaires or entire evaluation processes.